Social Aspects in Southern Kurdistan from the Perspective of the Press (1991-1998) - Saadi Uthman Haruti; Parzhin Jalal Nadr (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The years between (1991- 1998) is an important and crucial historical period for southern Kurdistan. Because it witnessed the establishment of Kurdistan regional government and overcoming the obstacle of civil war. This period was also left a clear mark on the complex of aspects of life in the region, including the social aspect. This research has been devoted to an important topic within this aspect, which are social phases. This is based on the information of the newspapers and magazines which issued in the region during this period. Considering that the press is the miror of the times. The research consists of three themes: in the first theme we addressed the customs and traditions of society as well as the popular believs prevailing at the time. The second theme is study the status of women and determines their importance in society, which has witnessed remarkable development compared to previous years. In the third theme was devoted to talking about games, holidays and social events, which are held in all societies for entertainment and expression of gladness.